Recent advances in indoline synthesis. Issue 14 (5th April 2019) - Silva, Thiago S.; Rodrigues, Manoel T.; Santos, Hugo; Zeoly, Lucas A.; Almeida, Wanda P.; Barcelos, Rosimeire C.; Gomes, Ralph C.; Fernandes, Fábio S.; Coelho, Fernando
Abstract: Indoline is an important structural motif present in several biologically active compounds from both natural and synthetic origins. The occurrence of this heterocyclic unity in these compounds is closely related to the biological activities they exhibit. This fact stimulated efforts that have been made worldwide to develop new synthetic approaches to prepare indolines. In this paper we reviewed critically the methods for indoline synthesis developed in the last years (from 2010 to 2018). Graphical abstract: Image 1